THE EXPORT OF FURNITURE FROM ROMANIA AT PRESENT - Silvia PUIU; Bogdan Andrei BUDICĂ; Dalina OCHETAN; Florin BUDICĂ (Management & Marketing)
The export of furniture always represented a profitable domain for Romania. The current research provides a pertinent analysis with numbers for the situation of the export in the furniture industry. The article proposes a few important measures that should be considered by the Romanian manufacturers of furniture in the further period, in order to reestablish the export activity and hence the wood processing industry.